2017
DOI: 10.3762/bjoc.13.79
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of D-manno-heptulose via a cascade aldol/hemiketalization reaction

Abstract: A [4 + 3] synthesis of D-manno-heptulose is described. The cascade aldol/hemiketalization reaction of a C4 aldehyde with a C3 ketone provides the differentially protected ketoheptose building block, which can be further reacted to furnish target D-manno-heptulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…De novo synthesis of the key 6-deoxy- d - manno -heptose building block 16 started from the first aldol reaction (Scheme ). d -Proline (0.5 equiv)-catalyzed aldol reaction of ketone 6 with 2,2-dimethoxyacetaldehyde 7 in DMSO afforded 2,3- anti -β-hydroxyl ketone 8 in 67% yield (de = 89%, ee = 78%) in multigram scale . Notably, replacement of DMSO with DMF or reducing the amount of d -proline led to a decreased yield of the aldol product.…”
Section: Resultsmentioning
confidence: 99%
“…De novo synthesis of the key 6-deoxy- d - manno -heptose building block 16 started from the first aldol reaction (Scheme ). d -Proline (0.5 equiv)-catalyzed aldol reaction of ketone 6 with 2,2-dimethoxyacetaldehyde 7 in DMSO afforded 2,3- anti -β-hydroxyl ketone 8 in 67% yield (de = 89%, ee = 78%) in multigram scale . Notably, replacement of DMSO with DMF or reducing the amount of d -proline led to a decreased yield of the aldol product.…”
Section: Resultsmentioning
confidence: 99%
“…2 Recently, it was found that fluorinated heptulose analogues functioned as tools for the noninvasive imaging of GLUT2-expressing insulin-producing cells by 19 F magnetic resonance imaging ( 19 FMRI). 3 In order to evaluate their spectrum of potential biological activities, ketoheptose analogues have been accessed by either chemical 1,4 or enzymatic 5 methods, with fluorinated carbohydrates as prominent tools to study various biochemical processes including structural and mechanistic investigations, 6 radio-labeling, 7 lectin–carbohydrate interactions, 8 and carbohydrate lipophilicity. 9 Further functionalization of ketoheptoses will provide access to mechanistic probes such as C-glycosides or analogues of glucose 6-phosphate (G6P) or glucose 1-phosphate (G1P).…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of l , d -Hep building block 2 started from l -lyxose 8 (Scheme ). Thus, treatment of 8 with ethanethiol with the aid of hydrochloric acid and subsequent reaction with 2,2-dimethoxypropane under the promotion of pyridinium p -toluenesulfonate afforded 4,5- O -isopropylidene-protected l -lyxose derivative 10 in 83% yield over two steps . The 3-hydroxyl group of 2,3-diol 10 was regioselectively protected with TBSCl in the presence of imidazole in DMF to give alcohol 11 in excellent yield (93%).…”
mentioning
confidence: 99%